Precision medicine: integration of genetics and functional genomics in prediction of bronchiolitis obliterans after lung transplantation. Issue 3 (May 2019) - Luijk, Bart; Vos, Robin; van Moorsel, Coline H.M.
Abstract : Purpose of review: Lung transplantation (LTx) can be a life saving treatment in end-stage pulmonary diseases, but survival after transplantation is still limited. Posttransplant development of chronic lung allograft dysfunction with bronchiolits obliterans syndrome (BOS) as the major subphenotype, is the main cause of morbidity and mortality. Early identification of high-risk patients for BOS is a large unmet clinical need. In this review, we discuss gene polymorphisms and gene expression related to the development of BOS. Recent findings: Candidate gene studies showed that donor and recipient gene polymorphisms affect transplant outcome and BOS-free survival after LTx. Both selective and nonselective gene expression studies revealed differentially expressed fibrosis and apoptosis-related genes in BOS compared with non-BOS patients. Significantly, recent microarray expression analysis of blood and broncho-alveolar lavage suggest a role for B-cell and T-cell responses prior to the development of BOS. Furthermore, 6 months prior to the development of BOS differentially expressed genes were identified in peripheral blood cells. Summary: Genetic polymorphisms and gene expression changes are associated with the development of BOS. Future genome wide studies are needed to identify easily accessible biomarkers for prediction of BOS toward precision medicine.